2015
DOI: 10.1080/13548506.2015.1058959
|View full text |Cite
|
Sign up to set email alerts
|

A model of caregiver paediatric HIV disclosure decision-making

Abstract: Many of the over 3 million HIV-positive children will only be told of their status as adolescents. Knowing one’s status may increase treatment adherence, reduce onward HIV transmission, increase trust in caregivers, and maximise available support. Yet deciding whether, what, how, and when to tell HIV-positive children about their condition, is challenging for caregivers. We systematically review HIV disclosure theories before presenting a process model of caregiver paediatric HIV disclosure decision-making. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
(70 reference statements)
3
15
0
Order By: Relevance
“…Study findings showed that, overall, biological mothers and relatives were more likely to discourage APHIV from disclosing their HIV status than adoptive or foster parents. This finding is consistent with research that found biological parents were less likely to disclose their child’s HIV status than adoptive parents because of concerns of secondary disclosure and fears of HIV-related stigma/discrimination (Evangeli & Kagee, 2016; Santacroce et al, 2002). Further, Michaud et al (2009) found that adolescents with HIV whose parents were also HIV-positive were less likely to disclose their HIV status to others.…”
Section: Discussionsupporting
confidence: 89%
“…Study findings showed that, overall, biological mothers and relatives were more likely to discourage APHIV from disclosing their HIV status than adoptive or foster parents. This finding is consistent with research that found biological parents were less likely to disclose their child’s HIV status than adoptive parents because of concerns of secondary disclosure and fears of HIV-related stigma/discrimination (Evangeli & Kagee, 2016; Santacroce et al, 2002). Further, Michaud et al (2009) found that adolescents with HIV whose parents were also HIV-positive were less likely to disclose their HIV status to others.…”
Section: Discussionsupporting
confidence: 89%
“…Given the likely importance of anxiety about disclosing one’s HIV status, it is surprising that explanatory models of HIV disclosure have rarely included anxiety as a central construct. A recent systematic review of HIV disclosure models [27] found that individual cognitive determinants of HIV disclosure were commonly cited in models (e.g., self-efficacy and perceived disclosure risks and benefits), but affect, including anxiety, was not. Indeed, neither the presence of anxiety nor how it is develops and can be maintained has been included in HIV disclosure theories.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of stigma from others also leads to selfstigmatisation, making it difficult for caregivers to accept their own diagnosis, and in turn projecting that unacceptance and stigma onto their child (13,23,39). This emphasises the need to equip healthcare providers to prepare and support caregivers throughout the disclosure process (27,28,43,44,47).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 19, 2021. ; https://doi.org/10.1101/2021.10.14.21264620 doi: medRxiv preprint Guiding caregivers through disclosure 4 untimely disclosure of HIV status to others; exposure of the caregiver's "personal secrets"; and caregiver's lack of knowledge on how and when to approach the disclosure questions (4,13,16,17,(22)(23)(24)(25)(26)(27). A recent study in Ghana (28) reported that caregivers lacked knowledge on how to disclose to their children, and that this poor knowledge was the main reason for delayed disclosure.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%